Fast and Stable N‐Terminal Cysteine Modification through Thiazolidino Boronate Mediated Acyl Transfer. (2nd July 2020) - Li, Kaicheng; Wang, Wenjian; Gao, Jianmin
Abstract: We report a novel conjugation of N‐terminal cysteines (NCys) that proceeds with fast kinetics and exquisite selectivity, thereby enabling facile modification of NCys‐bearing proteins in complex biological milieu. This new NCys conjugation proceeds via a thiazolidine boronate (TzB) intermediate that results from fast ( k 2 : ≈5000 m −1  s −1 ) and reversible conjugation of NCys with 2‐formylphenylboronic acid (FPBA). We designed a FPBA derivative that upon TzB formation elicits intramolecular acyl transfer to give N‐acyl thiazolidines. In contrast to the quick hydrolysis of TzB, the N‐acylated thiazolidines exhibit robust stability under physiologic conditions. The utility of the TzB‐mediated NCys conjugation is demonstrated by rapid and non‐disruptive labeling of two enzymes. Furthermore, applying this chemistry to bacteriophage allows facile chemical modification of phage libraries, which greatly expands the chemical space amenable to phage display. Abstract : Fast and dynamic thiazolidine boronate (TzB) formation followed by an acyl‐transfer reaction enables facile N‐terminal cysteine modification with single‐digit micromolar concentrations of labeling reagents and exquisite selectivity. The utility of this reaction is demonstrated by non‐disruptive labeling of enzymes as well as bacteriophage to generate chemically modified phage libraries.